3D-printed poly-ε-caprolactone-CaCO3-biocomposite-scaffolds for hard tissue regeneration - R. Neumann; J. Neunzehn; C. Hinueber; T. Flath; F. P. Schulze; H-P. Wiesmann (eXPRESS Polymer Letters, 2019)
Adopting the beneficial chemical composition of mineral bone grafts and the interesting biomedical properties of the approved polycaprolactone, versatile manufacturing processes offering a near-net-shape fabrication and cost-effective scalability, has been used to fabricate highly porous polymer-ceramic biocomposite scaffolds with different amounts of the inorganic component CaCO3 by molded casting and fused deposition modelling. The mechanical properties and surface characteristics were evaluated after several steps of degradation by means of compression tests and scanning electron microscopy, respectively. Calcium release has been determined over a period of 4 weeks and the calcium phosphate phase formation on the surface was observed and validated by energy dispersive x-ray spectroscopy. The established production path and the use of the material combination polycaprolactone and calcium carbonate has enormous potential to manufacture individual and application-oriented open-porous scaffolds for hard tissue replacement.